The impact of outgassing on the nano-oxides kinetics of ferritic oxide dispersion strengthened steel. (December 2022) - Spartacus, Gabriel; Malaplate, Joël; De Geuser, Frédéric; Sornin, Denis; Mouton, Isabelle; Guillou, Raphaëlle; Deschamps, Alexis
Abstract: Oxide Dispersion Strengthened (ODS) steels are studied for their application in fission and fusion nuclear power plants. These steels are processed by powder metallurgy involving a high energy milling of Fe-Cr with oxides powders, followed by outgassing and hot consolidation. The temperature increase during these last two stages triggers the precipitation of a fine dispersion of nano-oxides. The outgassing stage is generally conducted at temperature between 300 and 800 °C for several hours, which can already trigger the formation of nano-oxides, and thus may have an influence on the final nano-oxide characteristics. In this work we assess the nano-oxides size by Small Angle X-Ray Scattering (SAXS) and get insight on the nano-oxides chemical and structural properties by comparison between SAXS and Atom Probe Tomography (APT) during a thermal treatment at 700 °C for 5 h, simulating the outgassing stage. We show that despite that the nano-oxides slightly grow during the 700 °C heating, the final properties of the nano-oxides in term of size and number density are extremely close to those where no 700 °C isothermal was applied. Moreover, the growth rate of the nano-oxides is surprisingly higher at 700 °C than 1100 °C. APT and SAXS comparison shows that the nano-oxides do not stabilize in terms of stoichiometry and structure in the studied conditions, and that a small quantity of Al remain in the precipitates during this 700 °C isothermal treatment. Both of these factors could influence the nano-oxides kinetics at low temperature. Graphical Abstract: ga1 Highlights: The outgassing shows no influence on the final nano-oxides size and number density. No stabilization of the nano-oxides is observed at 700 °C after 5 h isothermal. The nano-oxides growth rate is surprisingly higher at 700 °C than at 1100 °C. Nano-oxides contain Al on the 700 °C isothermal, which is removed after heating at 1100 °C. TiC or Ti(C, N) is likely to form after the outgassing, between 700 and 1100 °C.